2019
DOI: 10.1021/acs.jpcc.8b10708
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Optical Properties of Designed Photo-Efficient Indoline-Based Dye-Sensitizers with D–A−π–A Framework

Abstract: Seven D−A−π−A-based indoline (IND) dyes that were designed via quantitative-structure−property relationship modeling have been comprehensively investigated using computational approaches to evaluate their prospect of application in future dye-sensitized solar cells (DSSCs). An array of optoelectronic properties of the isolated dye and dyes adsorbed on a TiO 2 cluster that simulates the semiconductor were explored by density functional theory (DFT) and time-dependent DFT methods. Light absorption spectra, verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 67 publications
0
32
0
Order By: Relevance
“…To facilitate an efficient electron injection at the interface and impede the undesired recombination of charges, the HOMO energies of should be more negative than the redox potential (−4.8 eV) while the LUMO level must be higher than the conduction band edge (−4.05 eV) of the intended semiconductor [20] . The results given in Figure 3 and Table 1 demonstrated that the HOMO energies of the studied dyes are in the range between −5.78 eV and −6.01 eV which are helpful to the spontaneity of regeneration of the synthesized‐dye.…”
Section: Resultsmentioning
confidence: 99%
“…To facilitate an efficient electron injection at the interface and impede the undesired recombination of charges, the HOMO energies of should be more negative than the redox potential (−4.8 eV) while the LUMO level must be higher than the conduction band edge (−4.05 eV) of the intended semiconductor [20] . The results given in Figure 3 and Table 1 demonstrated that the HOMO energies of the studied dyes are in the range between −5.78 eV and −6.01 eV which are helpful to the spontaneity of regeneration of the synthesized‐dye.…”
Section: Resultsmentioning
confidence: 99%
“…30 Thus, metal-free organic sensitizers have drawn greater attention over metal-based organic sensitizers due to their low toxicity, high structural flexibility, environment friendly nature, high MECs, and facile synthesis. 31,32 It is to be noted that previously, several chromophores such as indoline, 33,34 coumarin, 35,36 phenothiazine, 37,38 carbazole, 39,40 triarylamine, 41,42 tetrathiafulvalene, 43,44 etc were used in the assembly of organic sensitizers. Better structure-property relationship elucidation will encourage the better use of these dyes in DSSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The systematical theoretical study of seven D−A−π−A-based indoline (IND) dyes (Fig. 33a) was comprehensively investigated via quantitative-structure−property relationships to evaluate their prospect of application in DSSCs [195]. Adapted with permission from [195].…”
Section: Figure 28mentioning
confidence: 99%
“…33d). Considering the balance between the V OC and J SC (short circuit current), the IND3, IND5, and IND10 dyes were suggested as the most suited to be utilized as potential candidates for DSSC [195].…”
Section: Figure 28mentioning
confidence: 99%
See 1 more Smart Citation